The emerging evidences related to the Inter-relationship between COVID-19 and climate change: A scoping review perspective (Journal of Tropical Resources and Sustainable Science (JTRSS), 2022)
Coronavirus Disease 2019 (COVID-19) has affected a number of integral aspects and climate change is one of them. The inter-relationship between COVID-19 and climate change has garnered the interest among scholars across the globe to probe into the related emerging issues. With the escalating number of published articles, a pressing need is present to map and review all available studies in order to capture comprehensive and organised views for future scholars to draw upon the existing pattern of the interchanging correlation between COVID-19 and climate change. This scoping review is guided by a primary research question - what is the inter-relationship between COVID-19 and climate change. Related articles and documents were retrieved from Scopus, Science Direct, and Google Scholars databases. The thematically analysis data were classified into four emerging themes: (1) reduced air pollution, (2) low carbon emission, (3) the impact of temperature and humidity variation on COVID-19, and (4) the impact of air pollution on COVID-19. Variances in the outcomes, particularly on the effects of temperature, humidity, and polluted air on COVID-19, suggest further exploration endeavours. Essentially, the economic impact exerted by COVID-19 and its overall effect on budget to combat climate change remain untapped.
Keywords: climate change; COVID-19; scoping review; air pollution; low carbon habit; temperature; humidity